SPECTROPHOTOMETRIC DETERMINATION OF CEFPIROME IN PHARMACEUTICAL PREPARATION - CHAFLE, DILIP M (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A simple, sensitive and precise visible spectrophotometric method has been proposed for the determination of cefpirome (CFM) in pure and oral injectable dosage form. Methods: A spectrophotometric method is based on the formation of stable red color product by oxidation of drugs by ferric nitrate and subsequent complexation with 1, 10 – phenanthroline with maximum absorption at 515 nm. Result: The red color complex was formed between Fe (II) and 1, 10 – phenanthroline after reduction of Fe (III) to Fe (II) in the presence of CFM drug. The phosphoric acid solution was used only for quenching the complex formation reaction. Several parameters such as the maximum wavelength of absorption, the volume of reagents, sequence of addition and effect of temperature and time of heating were optimized to achieve high sensitivity, stability and reproducible results. Under the optimum conditions, linear relationship with good correlation coefficient (0.994) was found over the concentration range from 0.20 to 6.00 μg/mL with a molar extinction coefficient 7.7813 × 104 L/mol/cm, limit of detection 0.2026 and limit of quantification 0.6141 μg/mL, respectively. Conclusion: The proposed method was evaluated statistically for linearity, accuracy, and precision in terms of standard deviation, percentage recovery, percentage error and relative standard deviation. The proposed method can be applied for the routine estimation of CFM in the laboratory.